The work function algorithm for the paging problem - Zhang, Wenming; Hu, Huan; Cheng, Yongxi; Li, Hongmei; Wang, Haizhen (Theoretical computer science, 2022)
The paging problem is that of deciding which pages to keep in a memory of k pages in order to minimize the number of page faults in a two-level store. It is a special case of the famous k-server problem. In this paper, we firstly show that WFA is kM/m-competitive for the k-server problem where the distances between two points are all in [m,M] (0<m≤M), and thus WFA is k-competitive for the paging problem. And we further show that the well known FIFO for the paging problem is just a special case of WFA.